NILAI KARAKTER TOKOH PADA KUMPULAN CERITA RAKYAT DAERAH SIULAK KABUPATEN KERINCI KARYA ZARMONI (KAJIAN ANALISIS ISI) - Ningsih, Wahyu Setia; Sumiharti, Sumiharti; Supriyati, Supriyati (Universitas Batanghari, 2023)
The purpose of this study was to describe the character values of the figures in the collection of Siulak Regional Folklore, Kerinci Regency by Zarmoni. This research is a qualitative descriptive study. The data in this study are in the form of excerpts of sentences in which there are character values in the collection of Siulak Regional Folklore, Kerinci Regency by Zarmoni. The approach that the writer will use in this research is a structural approach. The results of this study can be concluded that the findings in the form of quotations consist of 54 quotations in which there are character values of figures who use the theory of the Ministry of National Education. There are 27 quotes of the character values of religious figures, there are 13 quotes of the character values of social care figures, there are 9 quotes of the character values of the people of responsibility and there are 5 quotes of the values of the character of hard work in the Siulak Regional Folklore of Kerinci Regency by the writer Zarmoni found.